Chronovaccination: Harnessing circadian rhythms to optimize immunisation strategies - Otasowie, Claire O.; Tanner, Rachel; Ray, David W.; Austyn, Jonathan M.; Coventry, Brendon J. (Frontiers in Immunology, 2022)
Vaccination, as a public health measure, offers effective protection of populations against infectious diseases. Optimising vaccination efficacy, particularly for higher-risk individuals, like the elderly whose immunocompromised state can prevent the development of robust vaccine responses, is vital. It is now clear that 24-hour circadian rhythms, which govern virtually all aspects of physiology, can generate oscillations in immunological responses. Consequently, vaccine efficacy may depend critically on the time of day of administration(s), including for Covid-19, current vaccines, and any future diseases or pandemics. Published clinical vaccine trials exploring diurnal immune variations suggest this approach could represent a powerful adjunct strategy for optimising immunisation, but important questions remain to be addressed. This review explores the latest insights into diurnal immune variation and the outcomes of circadian timing of vaccination or ‘chronovaccination’.